PENGGUNAAN KKBMM UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSEMPLUM PADA PESERTA DIDIK KELAS IX B SMP NEGERI 1 GABUS KABUPATEN GROBOGAN - SUHARTI SUHARTI (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2021)
The aims of this study are 1) to describe the learning process of writing exemplum texts with KKBMM in class IX B students of SMP Negeri 1 Gabus, Grobogan Regency in the first semester of the 2015/2016 academic year; 2) describe the improvement of writing skills in exemplum text with KKBMM in class IX B students of SMP Negeri 1 Gabus, Grobogan Regency in the first semester of the 2015/2016 academic year; and 3) describe the change in attitude of students in class IX B of SMP Negeri 1 Gabus, Grobogan Regency in the first semester of the 2015/2016 academic year in learning to write exemplum texts with KKBMM. The research site is at SMP Negeri 1 Gabus. The time of the study was from August to November 2015. The research subjects were students of class IX B SMP Negeri 1 Gabus in the 2015/2016 academic year. Collecting data by recording techniques, self-assessment, practice tests, and observations. CAR is carried out in 2 cycles. The learning process with KKBMM in writing exemplum texts has developed. Interest in learning, activeness, enthusiasm, seriousness, and student responses develop for the better. The percentage of questionnaire results in the first cycle was 67% and in the second cycle increased to 80%. Learning outcomes in the form of students' skills in learning to write exemplum texts have increased. In the pre-cycle students who finished studying were 21 (58%), the first cycle was 27 (75%), and the second cycle was 32 (89%). The attitude of students has changed for the better. The average value of attitudes towards religious teachings adopted in the pre-cycle was 2.38 (enough), in the first cycle it was 2.62 (good), and in the second cycle it was 3.10 (good). The average value of honesty in the pre-cycle is 2.26 (enough), in the first cycle it becomes 2.49 (enough), and in the second cycle it becomes 3.14 (good). The average value of self-confidence in the pre-cycle was 2.19 (enough), in the first cycle it was 2.48 (enough), and in the second cycle it was 3.03 (good). In cycle II, the percentage of success in respecting religious teachings is 94%, honesty is 89%, and self-confidence is 83%. ABSTRAKTujuan penelitian ini adalah 1) mendeskripsikan proses pembelajaran menulis teks eksemplum dengan KKBMM pada peserta didik kelas IX B SMP Negeri 1 Gabus, Kabupaten Grobogan semester I tahun pelajaran 2015/2016; 2) mendeskripsikan peningkatan keterampilan menulis teks eksemplum dengan KKBMM pada peserta didik kelas IX B SMP Negeri 1 Gabus, Kabupaten Grobogan semester I tahun pelajaran 2015/2016; dan 3) mendeskripsikan perubahan sikap peserta didik kelas IX B SMP Negeri 1 Gabus, Kabupaten Grobogan semester I tahun pelajaran 2015/2016 dalam pembelajaran menulis teks eksemplum dengan KKBMM. Tempat penelitian di SMP Negeri 1 Gabus. Waktu penelitian yaitu bulan Agustus sampai dengan November 2015. Subjek penelitian adalah siswa kelas IX B SMP Negeri 1 Gabus tahun pelajaran 2015/2016. Pengumpulan data dengan teknik perekaman, penilaian diri, tes praktik, dan observasi. PTK dilaksanakan dalam 2 siklus. Proses pembelajaran dengan KKBMM dalam menulis teks eksemplum mengalami perkembangan. Minat belajar, keaktifan, semangat, keseriusan, dan respon peserta didik berkembang menjadi lebih baik. Persentase hasil angket pada siklus I sebesar 67% dan pada siklus II meningkat menjadi 80%. Hasil belajar berupa keterampilan peserta didik dalam pembelajaran menulis teks eksemplum mengalami peningkatan. Pada prasiklus peserta didik yang tuntas belajar sebanyak 21 (58%), siklus I sebanyak 27 (75%), dan siklus II sebanyak 32 (89%). Sikap peserta didik mengalami perubahan menjadi baik. Rata-rata nilai sikap menghayati ajaran agama yang dianut pada prasiklus sebesar 2,38 (cukup), pada siklus I menjadi 2,62 (baik), dan pada siklus II menjadi 3,10 (baik). Rata-rata nilai sikap jujur pada prasiklus 2,26 (cukup), pada siklus I menjadi 2,49 (cukup), dan pada siklus II menjadi 3,14 (baik). Rata-rata nilai sikap percaya diri pada prasiklus sebesar 2,19 (cukup), pada siklus I menjadi 2,48 (cukup), dan pada siklus II menjadi 3,03 (baik). Pada siklus II persentase keberhasilan sikap menghargai ajaran agama yang dianut sebesar 94%, sikap jujur sebesar 89%, dan sikap percaya diri sebesar 83%.